2016
DOI: 10.7150/jca.14713
|View full text |Cite
|
Sign up to set email alerts
|

AKT-STAT3 Pathway as a Downstream Target of EGFR Signaling to Regulate PD-L1 Expression on NSCLC cells

Abstract: While cancer development and progression can be controlled by cytotoxic T cells, it is also known that tumor-specific CD8+T cells become functionally impaired by acquiring a group of inhibitory receptors known as immune checkpoints. Amongst those, programmed death-1 (PD-1) is one of the most recognized negative regulators of T cell function. In non-small lung cancers (NSCLCs), the aberrant activation of epidermal growth factor receptor (EGFR) is known to induce PD-L1 expression and further the treatment with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 37 publications
1
69
0
Order By: Relevance
“…In addition, we also found that IFN‐γ‐induced increased phosphorylation of STAT3. Activation of STAT3 as a downstream target of EGFR signaling regulated PD‐L1 expression . However, STAT3 as a downstream target of IFN‐γ does not affect IFN‐γ‐induced PD‐L1 expression in head and neck cancer .…”
Section: Discussionmentioning
confidence: 96%
“…In addition, we also found that IFN‐γ‐induced increased phosphorylation of STAT3. Activation of STAT3 as a downstream target of EGFR signaling regulated PD‐L1 expression . However, STAT3 as a downstream target of IFN‐γ does not affect IFN‐γ‐induced PD‐L1 expression in head and neck cancer .…”
Section: Discussionmentioning
confidence: 96%
“…In bladder cancer, YAP1 expression is significantly associated with advanced clinicopathological stage and poor prognosis . YAP1 promotes bladder cancer cell growth and migration by cooperating with other molecules such as ANKRD17, KLF5, and COX2 …”
Section: Yap1 In Cancer Developmentmentioning
confidence: 99%
“…This postulate is based on the observations that PD-L1 expression in tumor cells is induced by IFN-γ (Cheng et al, 2007; Dondero et al, 2016; Iwai et al, 2002; Muhlbauer et al, 2006), and IFN-γ signaling is dependent on sphingolipid metabolism (Bajwa et al, 2017; Ottenlinger et al, 2016; Seo, Alexander, & Hahm, 2011; Wakita, Nishimura, Tokura, Furukawa, & Takigawa, 1996). Furthermore, Akt- (Abdelhamed, Ogura, Yokoyama, Saiki, & Hayakawa, 2016; Atefi et al, 2014; Dong et al, 2016; Lastwika et al, 2016; Song et al, 2013; Yang et al, 2017; Zhao et al, 2017), NF-kB- (Gowrishankar et al, 2015), and TNFα- (Wang et al, 2017) signaling induce PD-L1 expression, and all of these pathways are regulated by sphingolipid signaling. Therefore, manipulation of tumor immunology using SK inhibitors is an unexplored potential new approach to improved cancer therapy.…”
Section: Sphingosine Kinases As Targets For Anticancer Drugsmentioning
confidence: 99%